Dynamic Compression Properties and Deterioration of Red-Sandstone Subject to Cyclic Wet-Dry Treatment - Du, Bin; Wu, Guangming; Bai, Haibo (Advances in civil engineering, 2019)
Rock engineering is usually associated with impact loads induced by blasting, drilling, vibration, or earthquake. In the engineering fields of tunnelling, slopes, dams, and mining, rocks are always subjected to cyclic wet-dry caused by periodical variation in moisture. To study cyclic wet-dry effects on dynamic compression properties and deterioration of red-sandstone, physical tests and dynamic and static tests were conducted after 0, 5, 10, 15, and 20 wet-dry cycles. Changes in physical and mechanical parameters, including P-wave velocity, density, and static and dynamic compression strength, were determined. Deterioration of red-sandstone caused by wet-dry cycles was verified through physicomechanical parameters, and the microscopic features were scanned by SEM techniques. Experimental results showed that the dynamic compression strength increased with the loading rate, but decreased with the increase of wet-dry cycles. In terms of the loading rate, the decay function model was proposed to evaluate the long-term dynamic compression strength of red-sandstone against cyclic wet-dry action. Besides, the function of the loading rate was obtained. Parameters of two models, decay constant and half-life values, were measured accurately.